Application of conical profile spindle-mandrel joints in multi-purpose machines - V. A. Ilyinykh (Омский научный вестник)
The article deals with the solution of the problem of improving the quality of torque transmission connections of spindle units of multi-purpose machines. The aim of the work is to determine the contact stiffness of the spindle-mandrel joints of various types, based on the conducted simulation experiments of the assembly and disassembly process of auxiliary tools of various structural forms, in conditions of reusable replacements. A comparative analysis of the mathematical expectations of contact stiffness of traditional and non-traditional conical profile split joints based on an equiaxial contour with a number of faces equal to three under external loading conditions is performed. The results obtained allow us to predict the quality indicators of multi-purpose machines in the design of quick-release connections.